2019
DOI: 10.1371/journal.pone.0210712
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Fc fusion protein misfolding: A three-phasic cultivation experimental design

Abstract: Cell culture process optimization is a critical solution to most of the challenges faced by the pharmaceutical manufacturing. One of the major problems encountered in large-scale production of therapeutic proteins is misfolded protein production. The accumulation of misfolded therapeutic proteins is an immunogenic signal and a risk factor for immunogenicity of the final product. The aim of this study was the statistical optimization of three-phasic temperature shift and timing for enhanced production of correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In the literature, Fc‐fusion size heterogeneity is known to be caused by proteinogenic fragments, resulting from the activity of host cell‐related proteases such as cysteine endopeptidase (Mitsuo et al, 1990) or matrix metalloproteases (Sandberg et al, 2006). Several mitigation strategies have been developed including changes in bioprocess conditions (culture temperature and time, partial pressure of CO 2 [Chakrabarti et al, 2016; Ghorbani Aghdam et al, 2019; Menthe et al, 2022]) or change in cell culture media composition (addition of ferric citrate, or protease inhibitor cocktail [Chakrabarti et al, 2016; Hou et al, 2019]). Other recent studies on complex N‐ and C‐ terminal Fc‐fusion proteins (Datola et al, 2023) showed that LMW proteoforms may be caused by reshuffled disulfide bridges and can lead to protein misfolding responsible for aggregation and precipitation (Zhang et al, 2011), further affecting the biological activity and safety of the therapeutic molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, Fc‐fusion size heterogeneity is known to be caused by proteinogenic fragments, resulting from the activity of host cell‐related proteases such as cysteine endopeptidase (Mitsuo et al, 1990) or matrix metalloproteases (Sandberg et al, 2006). Several mitigation strategies have been developed including changes in bioprocess conditions (culture temperature and time, partial pressure of CO 2 [Chakrabarti et al, 2016; Ghorbani Aghdam et al, 2019; Menthe et al, 2022]) or change in cell culture media composition (addition of ferric citrate, or protease inhibitor cocktail [Chakrabarti et al, 2016; Hou et al, 2019]). Other recent studies on complex N‐ and C‐ terminal Fc‐fusion proteins (Datola et al, 2023) showed that LMW proteoforms may be caused by reshuffled disulfide bridges and can lead to protein misfolding responsible for aggregation and precipitation (Zhang et al, 2011), further affecting the biological activity and safety of the therapeutic molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Another extensive process development study was performed to obtain correctly folded erythropoietin (EPO) Fc‐fusion protein (Ghorbani Aghdam et al, 2019). The final process included a two‐step temperature shift, which led to an upregulation of genes encoding unfolded protein response specific transcriptional activators and ER‐resident proteins associated with processing and folding in the secretory compartments (Torres et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these production issues can be influenced by the amino acid sequence of the produced protein [ 20 , 21 , 22 ], which is of particular concern for the efficient production of mutated SARS-CoV-2 RBD recombinant proteins. To overcome these challenges, engineering and optimisation approaches have been proposed [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Additionally, mammalian cells have become a favoured system to produce recombinant proteins for clinical and diagnostic applications because they allow proper post-translational modifications and protein folding [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In designing the recombinant multi-domain proteins, the fusion proteins are more prone to misfolding or assembling in an incorrect 3D shape when compared with a single-domain protein, as different peptide domains interact with each other in different ways. 29 To overcome this limitation, in silico analyses are performed to generate the recombinant fusion proteins followed by the protein modeling and Molecular Dynamic (MD) simulations. In the current report, molecular modeling of an antagonistic angiogenic fusion protein—ie, soluble ECD of human VEGFR-1 (sVEGFR-1) and human IL-2—uses threading assembly refinement to predict the 3D structure and energy minimization.…”
Section: Introductionmentioning
confidence: 99%